2020
DOI: 10.1111/tpj.14930
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure and marker–trait associations in East and West African Striga hermonthica with varying phenotypic response to Fusarium oxysporum f. sp. strigae isolates Foxy‐2 and FK3

Abstract: To examine the genetic basis for the variable susceptibility of Striga hermonthica from differing zones of sub-Saharan Africa to Fusarium oxysporum f. sp. strigae (Fos) isolates Foxy-2 and FK3, 10 S. hermonthica populations from Eastern and Western Africa were phenotyped for their susceptibility response to Foxy-2 and FK3, and then genotyped with 22 simple sequence repeat (SSR) markers. There is low genetic differentiation between East African and West African S. hermonthica populations (i.e. the proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Sorghum (Sorghum bicolor L. Moench) seeds (cultivar PI563294) were sampled from Maradi, Niger. Our previous research studies confirmed the susceptibility of this sorghum cultivar to S. hermonthica [5,6]. The S. hermonthica and sorghum seeds were separately surface-sterilized using sodium hypochlorite, Tween 20 ® and double distilled water (ddH 2 O), then air-dried, according to the procedure of Anteyi and Rasche [5,6].…”
Section: Methodsmentioning
confidence: 64%
See 3 more Smart Citations
“…Sorghum (Sorghum bicolor L. Moench) seeds (cultivar PI563294) were sampled from Maradi, Niger. Our previous research studies confirmed the susceptibility of this sorghum cultivar to S. hermonthica [5,6]. The S. hermonthica and sorghum seeds were separately surface-sterilized using sodium hypochlorite, Tween 20 ® and double distilled water (ddH 2 O), then air-dried, according to the procedure of Anteyi and Rasche [5,6].…”
Section: Methodsmentioning
confidence: 64%
“…Furthermore, in Nicotiana sylvestris, pollen germination inhibition started from 20 ng mL − 1 (0.055 μM) DAS at 26.7%, but at 200 ng mL − 1 (0.55 μM), it was completely inhibited [65]. Because the variable susceptibility of diverse S. hermonthica populations to Fos isolates has been a major drawback in biocontrol of S. hermonthica [5,7], the ability of DAS to consistently inhibit seed germination of diverse S. hermonthica populations in our study is a very interesting discovery. After DAS, T-2 was the second bestperforming exometabolite tested in our study, followed by Neo.…”
Section: Das Revealed Outstanding Suppression Of S Hermonthicamentioning
confidence: 99%
See 2 more Smart Citations